2023
DOI: 10.56553/popets-2023-0047
|View full text |Cite
|
Sign up to set email alerts
|

DeepSE-WF: Unified Security Estimation for Website Fingerprinting Defenses

Abstract: Website fingerprinting (WF) attacks, usually conducted with the help of a machine learning-based classifier, enable a network eavesdropper to pinpoint which website a user is accessing through the inspection of traffic patterns. These attacks have been shown to succeed even when users browse the Internet through encrypted tunnels, e.g., through Tor or VPNs. To assess the security of new defenses against WF attacks, recent works have proposed feature-dependent theoretical frameworks that estimate the Bayes erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Defense configurations. We follow the methodology of Veicht et al [44] and use default parameters for WF defenses, as suggested in their original papers. We used the WTF-PAD implementation from the WFES repository [5], and two versions of FRONT [14] with parameters: 𝑁 𝑐 = 𝑁 𝑠 = 1700 and π‘Š π‘šπ‘–π‘› = 1, π‘Š π‘šπ‘Žπ‘₯ = 14 for FRONT_T1, and 𝑁 𝑐 = 𝑁 𝑠 = 2500 for FRONT_T2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defense configurations. We follow the methodology of Veicht et al [44] and use default parameters for WF defenses, as suggested in their original papers. We used the WTF-PAD implementation from the WFES repository [5], and two versions of FRONT [14] with parameters: 𝑁 𝑐 = 𝑁 𝑠 = 1700 and π‘Š π‘šπ‘–π‘› = 1, π‘Š π‘šπ‘Žπ‘₯ = 14 for FRONT_T1, and 𝑁 𝑐 = 𝑁 𝑠 = 2500 for FRONT_T2.…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by Veicht et al [44], we assess the effectiveness of Tik-Tok and AutoKeras-generated models on a set of relevant WF defenses which are accompanied by high-fidelity simulators [15]. We use these simulators to generate defended traffic from the prerecorded undefended traces contained in the DS-19 dataset.…”
Section: Laboratory Setupmentioning
confidence: 99%
“…Gong et al [10] have recently compared the simulation and true implementation results for a set of WF defenses and reached the conclusion that simulators can accurately reflect the effectiveness of defenses on live traffic. We utilize the same defense simulators and configurations recently used in the work of Veicht et al [45], which focused on the security analysis of website fingerprinting defenses. We refer the reader to Appendix B for details on the defenses' parameters.…”
Section: Attacks and Defensesmentioning
confidence: 99%